POLYMORBIDITY IN CLINICAL PRACTICE - Uvarova, K. G.; Saprykina, M. M.; Ahmed, M. A.; Oyebamire, I. B.; Makienko, N. V.; Maltseva, M. S.; Kamenskaya, E. P.; Yabluchanskiy, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The interaction of diseases for their clinical features, severity type, quality of life of patients and preferable drug therapy are reviewed on the example of clinical case. Clinical examination, diagnosis and choice of optimal drug management are outlined in patient with polymorbid pathology.